A powerful software‐defined cyber‐physical system to expand CPS adoption. (12th July 2019) - Yu, Haisheng; Qi, Heng; Li, Keqiu
Summary: The cyber‐physical system (CPS) has become a promising direction that can enrich the interaction between people and people, people and objects, objects and objects in the physical world and the virtual world. Because of the development of CPS, the number and types of smart device connected to the Internet has rapidly increased, bringing with it the current issues of flexibility, efficiency, availability, security, and scalability of the Internet‐of‐Things (IoT) network. These problems are caused by the key mechanism of large‐scale distribution to the IoT network. In this article, we propose CPSS inspired by software‐defined networking (SDN) and service‐oriented architecture, which is a powerful software‐defined cyber‐physical system to solve the challenges of broader CPS adoption. CPSS has three complementary modules: application‐as‐a‐service (AAAS), network‐as‐a‐service (NAAS), and infrastructure‐as‐a‐service (IAAS). IAAS collects network information from a different set of controllers and devices and generates a domain‐wide network view. NAAS collects information from different domains and generates a global view, which helps data transmission between different domains and enables seamless switching between applications and infrastructure devices. AAAS provides personalized service for each user. To test CPSS, we develop a prototype system. Our experimental results show that CPSS can effectively control cyber‐physical system, and CPSS has greatly improved network latency, network throughput, and network reliability compared to traditional controller‐controlled CPS.